Fascism, Race, and Religion in Interwar Transylvania The Case of Father Liviu Stan (1910–1973) - Biliuṭă, Ionuṭ (2020)
This text discusses several aspects of the interwar history of the Orthodox Church in Romanian Transylvania through the lens of the early life and political achievements of Father Liviu Stan (1910-1973). By using a microhistorical approach, his life stands as proof of the ability of ideological reconversion to describe the various totalitarian challenges that defined the destiny of an entire generation of Orthodox theologians in the twentieth century. Rather than painting the biographical tapestry of Father Stan's life, the main focus of this text falls precisely on his interactions with various ideologies (Fascism and Communism), his ideological and professional reconversions, and Transylvanian Orthodox theologians’ ability to survive when confronted with various totalitarian challenges.
Keywords: Orthodox Church; Fascism; ideological reconversions; interwar Romania; Racism